Clinicians' views on the clinical utility of a revised definition of schema and its implications for the treatment of depression. (13th March 2014) - Howarth, Alan; Freeston, Mark; Reichelt, Katharina; James, Ian A.
Abstract: The main objectives of this study were to compare the perceived utility of two definitions of schema (i.e. a standard Beckian vs . a revised definition). Fifty clinicians with varying degrees of training in cognitive behavioural therapy (CBT) received a presentation on the Beckian definition of schema before completing two questionnaires, one assessing the perceived utility of the definition, and another assessing the targets they would address in therapy and the techniques they would use to do so, using the Beckian definition. They then received a presentation on a revised definition before completing the questionnaires again; this time in relation to the revised definition. In a non-inferiority analysis the revised definition was rated as possessing not less clinical utility than the Beckian definition and was indeed rated higher. More targets and techniques were selected following the revised definition, relative to the Beckian definition. Further, there was a significant interaction between definition and targets and techniques selected, with a greater increase in the targets and techniques that are consistent with the revised definition. The results were independent of experience within mental health and practising CBT therapists. The revised definition was perceived to have clinical utility and the use of it in therapy would lead to a wider range of targets being addressed while using a wider range of clinical techniques. Importantly, those targets and techniques relate specifically to the revised definition. The implications of the results and future areas of research are discussed.